2014
DOI: 10.1186/1471-2253-14-114
|View full text |Cite
|
Sign up to set email alerts
|

The caval index: an adequate non-invasive ultrasound parameter to predict fluid responsiveness in the emergency department?

Abstract: BackgroundFluid therapy is the first important step in patients with signs of shock but assessment of the volume status is difficult and invasive measurements are not readily available in the emergency department. We have investigated whether the respiratory variation in diameter of the inferior vena cava is a reliable parameter to predict fluid responsiveness in spontaneous breathing emergency department patients with signs of shock.MethodsAll patients admitted to the emergency department during a 15 week per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 29 publications
2
30
0
5
Order By: Relevance
“…To support the assertion that both IVC collapse and IVC diameter are determined by CVP, the one study which reported on their predictive accuracy for FR found them to have identical AUC's of 0.62, similar to that of CVP (19,25). Of note, the two studies in Table 1 which found even a modest predictive ability of IVC collapse included 38% and 50% of patients with baseline, overt hypovolemic insults respectively (29,31).…”
Section: Accepted Manuscriptmentioning
confidence: 59%
“…To support the assertion that both IVC collapse and IVC diameter are determined by CVP, the one study which reported on their predictive accuracy for FR found them to have identical AUC's of 0.62, similar to that of CVP (19,25). Of note, the two studies in Table 1 which found even a modest predictive ability of IVC collapse included 38% and 50% of patients with baseline, overt hypovolemic insults respectively (29,31).…”
Section: Accepted Manuscriptmentioning
confidence: 59%
“…Multiple studies in spontaneously ventilating adults have reported the accuracy of respiratory variation in IVC diameter as a predictor of fluid responsiveness, [34][35][36][37][38][39][40] with a pooled AUROC of 0.76. 24 The majority of these studies enrolled mixed patient populations, including those with trauma, dehydration and postoperative surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Two others yielded borderline results, with the authors commenting that the ''IVC cannot reliably predict FR'' in one 33 and ''caval index does not reliably predict FR'' in the other. 34 The first positive result comes from a study requiring patients to perform a standardized and quantitative inspiratory effort, 35 a technique that cannot be applied to patients who are dyspneic, supine, confused, or intubated, greatly limiting its applicability to critical care. The second 36 is a relatively large (n = 124) emergency department study, which yielded a strong positive result but was criticized for the use of a somewhat controversial tool to estimate FR (thoracic bioreactance), the late enrolment of patients (16 hr after presentation, having already received 4 L of fluid on average), and the low inter-rater reliability (0.67) between experts.…”
Section: Abdominal Factorsmentioning
confidence: 99%